THE IMPLEMENTATION OF CRIMINAL SANCTIONS IN CRIMINAL CODE AGAINST CRIMINAL ABORTION ACTION BASED ON JUSTICE VALUE - Hanuring Ayu Ardhani Putri (Jurnal Pembaharuan Hukum, 2017)
The right to life is one of the human rights listed in the Constitution of the State as described in Article 28 (a) of the 1945 Constitution of the Republic of Indonesia. Abortion often occurs in this village. The health expert has not yet given a definitive response, vaguely seen the agreement that abortion can be done by considering the cause, the future of the child and the psychological reason of the family, especially the mother, provided that it is done in ways that meet certain conditions and conditions. So also with social experts who have a view that is not much different from health experts. This study aims to analyze the rights of women from the perspective of human rights and the application of criminal sanctions for perpetrators of criminal acts of abortion. This research method using normative juridical, which both research data obtained from references of literature and applicable legislation, and analyze from court decision. It is concluded that the application of criminal sanction by Judge to perpetrator of abortion crime in Indonesia is still very low compared to criminal threat contained in Criminal Code.